Factors affecting the demand for national car in Kuching - Toh,, Su Siah Hazel (Universiti Malaysia Sarawak, 2006)
The main objective of this study is to determine the factors that affected the demand for national car in Kuching. The research had 100 sample size of respondents which answering the questionnaires that had been randomly distributed. The analysis methods used in this research include descriptive statistic analysis, reliability analysis and factor analysis. Empirical result shows that promotion and price had most significant relationship with the demand for national car in Kuching. Finally, this research also gives several suggestions for further research in the future.